Scalable uncertainty management : 10th International Conference, SUM 2016, Nice, France, September 21-23, 2016, proceedings /: 10th International Conference, SUM 2016, Nice, France, September 21-23, 2016, proceedings. (2016) - Unknown
No abstract available